Pengaruh Pengalaman Auditor dan Time Budget Pressure terhadap Kualitas Audit Pada Kantor Akuntan Publik di Jakarta Selatan - Hirim Tarihoran; Rosaidah Permanasari Sembiring; Eka Budi Yulianti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The unexpected performance of an auditor is extremely undesirable in the course of an audit, but errors in the presentation of financial statements have occurred due to the lack of experience and expertise of an auditor. Therefore, this study was conducted to analyze the Auditor's Experience and Time Budget Pressure on Audit Quality. Therefore, this study was conducted to analyze the Auditor's Experience and Time Budget Pressure on Audit Quality. This study used primary data obtained through the distribution of questionnaires to 64 auditor respondents working in South Jakarta's CAP. Based on the results of the data test using SPSS V.26 software, it showed that simultaneously independent variables, namely Auditor Experience and Time Budget Pressure, explained the effect on dependent variables, namely Audit Quality by 55.3% while the rest was 44.7% affected by other factors not included in this regression model. Partially the Auditor's Experience and Time Budget Pressure have a positive effect on the Quality of Audits.